Mean and intra‐seasonal variability simulated by NCEP Climate Forecast System model (version 2.0) during boreal winter: Impact of horizontal resolution. (12th March 2018) - Malviya, Shilpa; Mukhopadhyay, P.; Phani Murali Krishna, R.; Dhakate, Ashish; Salunke, Kiran
Abstract : Keeping in mind the inclination of modelling community towards high‐resolution models, analysis of MJO simulated by CFSv2 at three different horizontal resolutions with the finest being at 28 km is performed which indicates that merely increasing the resolution of the model does improve the skill unless the parameterization schemes are also retuned accordingly or include resolution dependencies. Abstract : This study demonstrates the fidelity of Climate Forecast System version 2 (CFSv2) in three horizontal resolutions: T62, T126 and T382, during boreal winter. As the Madden–Julian oscillation (MJO) is the major mode of variability during boreal winter, the emphasis of the study is on the fidelity of the models in capturing the MJO variability. CFSv2 shows moderate skill in simulating the intra‐seasonal oscillation and the skill is sensitive to the resolution of the model. Boreal winter mean precipitation shows the tendency of the model to overdo the double Intertropical Convergence Zone (ITCZ) that increases with resolution. Twenty to hundred days band‐pass‐filtered rainfall variances also indicate that the dominant variances are overestimated with increase in resolution. The characteristic eastwards propagation is not captured by the model at all the resolutions. In an attempt to understand the limitation of the model, composites of specific humidity are analysed which show that the model's moisture profile is rather better represented at lower resolution than the higher ones. Analyses of relative humidity profile as a function of rainfall rates show that all the model resolutions fail to reproduce the lower‐level moistening prior to deep convection. Observational studies have shown shallow convection to be responsible for this low‐level moistening. Furthermore, analysis of mean stratiform rainfall indicates that spectrum of rainfall variability is not simulated by the model and increasing the resolution could not improve the cloud processes. This study therefore indicates that the fundamental moist convective processes do not improve in the model and neither its bias in capturing the intra‐seasonal variability vis‐à‐vis MJO through increasing resolution. This can therefore be a basis for improving the moist convective processes with emphasis on the improvement of the shallow convection within boundary layer and also for the inclusion of scale dependencies in parameterized processes.